Ross syndrome: a case report - Mahata, Manoj Kr.; Ghosh, Saikat; Ghosh, K. C.; Bhattacharyya, R.; Mondal, G. P. (International Journal of Research in Medical Sciences, 2019)
Ross syndrome is a rare partial dysautonomic syndrome of unknown aetiology, characterized by segmental hypo/ anhidrosis associated with Holmes-Adie syndrome (tonic pupil and hypo/areflexia). The hypohydrosis or anhydrosis is patchy initially, later it becomes segmental or diffuse. This is due to affection of postganglionic cholinergic parasympathetic and sympathetic fibers involvement. There are a very few cases (approximately 50) have been reported in the literature since its original description. Author report a 22 years old male with classical features of Ross syndrome.